Reliability analysis of time series force plate data of community dwelling older adults - Bauer, Christoph; Gröger, Ines; Rupprecht, Roland; Meichtry, Andre; Tibesku, C.O.; Gaßmann, Karl-Günter (Archives of gerontology and geriatrics, 2010)
Frequency-based analysis of body sway has been used to distinguish between healthy young, healthyelderly adults and elderly adults with Huntingtons disease. Our aim was to assess the reliability of spectral-based outcomes of the centre of pressure (CoP) kinematics in order to determine if these outcomes could be tested for their capability to distinguish between elderly fallers and non-fallers in a future study. We have studied balance for 30 community dwelling healthy older adults 60 years or older. Four test conditions were used. Three successive trials were performed for each condition. CoP kinematics were estimated with a force platform with three strain gauges set in a triangular position. The frequency content of these signals was estimated. Intrasession correlation coefficients (ICC’s) were then calculated for all test conditions. The reliability of the selected parameters varied between low and high (ICC 0.652–0.939). The ICC’s for the narrow stance tests were higher compared to tests with normal standing conditions (0.771–0.94) to (0.652–0.865). The highest value was obtained in the high frequency band (0.939). These measures should be viewed with caution when screening geriatric patients because their reliability cannot always be assumed.
Keywords: Falls in elderly; Reliability; Posture; Balance